Competence and performance: evaluation and management of the education - João Mauro G. V. de Carvalho (Revista Sem Aspas, 2013)
This article aims to outline a critical refl ection about the Brazilian educational system, especially about the function performed by centralized methods of evaluation of the whole system (as in the case of ENEM and ENADE) as well as some possible consequence of this administrative organization on the formative process of the Brazilian students. Therefore, we resort to theoretical and methodological framework of Critical Theory, especially the concepts of cultural industry and semi-formation developed by Adorno, and its update in the educational fi eld, in the critique of teaching developed by the German pedagogue Andreas Gruschka and in the sociology of the curriculum carried out by the Brazilian educator Monica Ribeiro da Silva.